Editorial Special issue: Links in the air transport chain: Where and when does optimisation begin? - Voorde, Eddy van de (European Journal of Transport and Infrastructure Research, 2008)
The air transport sector has recently enjoyed a period of strong economic growth and boom, marked by the entry of new carriers, expanding business, and considerable profit-making. Clearly, though, this has not always been the case. What is more, in the first half of 2008, we have witnessed a new wave of mergers and takeovers, as well as bankruptcies and market exits, which would seem to suggest that the boom is over, for a while at least. As in the maritime sector, thought and action in the airline business have evolved rapidly in recent years, with respect to both passenger and freight transport. Increasingly, players are approaching the industry from the perspective of air transport chains. Prospective customers are no longer selecting airports and airlines on the basis of their individual merits, but because they belong to an air transport chain that meets their preferences maximally and corresponds to their willingness to pay. Hence, the success of those airports and airlines depends crucially on whether or not they belong to a successful air logistics chain. This process coincides with a degree of specialisation, air freight being a typical example. Whereas air freight used to be regarded as a ‘side product’ of passenger transport, there are now a number of carriers focusing exclusively on freight. Likewise, there are now airports (albeit smaller ones) who consider freight transport as their core business. This growing significance of full-freighter services has been occasioned by a combination of factors, including insufficient freight capacity and stricter safety regulations on passenger planes, a trend towards scale enlargement, and substantial imbalances between incoming and outgoing flows. It is important that research should stay apace with this rapid evolution in the airline industry. In the present issue of the European Journal of Transport Infrastructure Research, we pick up on the now widely accepted transport chain perspective. The six contributions focus on different links in the air transport chain, but without losing sight of interdependencies and the possibility of integration.